(untitled) (Vietnam Journal of Community Medicine, 2022)
The cross-sectional descriptive study aims to describe the 5S score and analyze some limitations. The study was conducted in June 2020 at Outpatient department, Binh Thanh Hospital, Ho Chi Minh City. The research results show that the average score in Sort is the lowest with 2.2 points, the highest in the Sustain is 4.2 points, and Shine 4.1 points. Through the research, some basic limitations have been noted in implementing 5S implementation at Outpatient department, Binh Thanh Hospital. Therefore, in order to improve 5S, the hospital needs to trainging 5S, have more accurate, scientific and large-scale assessment studies.